Public Relations Skills, Managerial Competencies, and Leadership Style in Community Learning Center Managers - Sa'diyah, Devi Merina Tuz; Zailani, Rinawati (Journal of Nonformal Education and Community Empowerment, 2024)
The public relations skill of a community learning center (CLC) manager is a mediation between the institution and the public which will affect how the public perceives the institution's image. Furthermore, the managerial competence of CLC managers is assessed as the expertise to place the right people to do the appropriate work so that the managerial process can be optimized. A CLC manager in Malang Raya carries out his duties and functions through various leadership styles ranging from directing, coaching, supporting, and delegating leadership styles. The study aims to measure the influence of public relations skills and managerial competence on the leadership style of CLC managers using quantitative research methods with a sample of 39 CLC managers in Malang Raya by distributing questionnaires in the google forms that have been tested for validity and reliability to collect data. The data that has been collected is tested using the SPPSS application. Then the research hypothesis was analysed using multiple regression analysis techniques which showed that public relation skill and managerial competence had a significant partial influence on the leadership style of CLC managers in Malang Raya. Furthermore, the leadership style of CLC managers in Malang Raya is also influenced simultaneously by the variables of public relations skills and managerial competence, this is evidenced by the results of the F test, namely Fcount 16.283> Ftable 3.25. Then the value of R2 shows that public relations skills and managerial competence affect the improvement of the leadership style of CLC managers by 79.3%. Based on this research, CLC managers in Malang Raya could improve their leadership by optimizing their public relations skills and managerial competencies. Consequently, the policy makers in the local area can optimize this through the implementation of various relevant technical guidance or training.